EFFECT OF TRIACONTANOL, NANO-ZINC, AND LIQUID ORGANIC FERTILIZER ON QUANTITATIVE AND QUALITATIVE CHARACTERISTICS OF LOCAL LEMON FRUITS - AL-Shujairy, Hussein; Al-Hadethi, Mustafa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The experiment was conducted during 2023 and 2024 growing seasons in a private orchard in Alexandria area in Babylon Governorate. study included three factors, first was spraying growth regulator triacontanol at three levels: no spraying (T0), spraying 10 mg.l-1 (T1), spraying 20 mg.L-1 (T2): second factor is spraying Nano-zinc at three levels (0, 50, 100 mg.L-1), as Z0, Z1, and Z2 respectively and third factor is adding liquid organic fertilizer at three levels (0, 50 , 100 ml. Tree-1) is represented by symbols O0, O1, O2  respectively. Spraying and adding process is carried out five times in spring season and three times in autumn season with an interval of 20 days between one spray and another. This is also case for addition and for two growing seasons. Coefficients were repeated three times in RCBD factorial experiment so trees number included in experiment was 81 trees. Experimental results showed that spraying triacontanol at 20 mg.L-1 and spraying Nano zinc at 100 mg.L-1 and adding liquid organic fertilizer at 100 ml.L-1 as an interaction treatment (T2Z2O2) gave best results in average fruit weight trait (92.00, 89.88) g , total tree yield (9.893, 12.000) kg.tree-1 , total fruits acidity (4.75,4.87) % , vitamin C fruit content (45.45,46.25) mg.100 ml-1 , GA3 leaves content (161.64) and IAA (39.24) μg g-1 FW for two growth seasons respectively compared to control treatment that gave lowest values.